Life Cycle Assessment of Metal Part Repair Using Directed Energy Deposition : A Comparison Between Arc- and Laser-Based Methods - Hörkkö, Jaakko (My University, 2025)
This bachelor’s thesis investigates the environmental performance of metal part repair using Directed Energy Deposition (DED), focusing on a comparison between arc-based (DED-Arc) and laser-based (DED-LB) methods. The analysis is based on a process-phase life cycle assessment (LCA), using energy consumption, material efficiency, and shielding gas use as key indicators. A real-world case involving the DED-LB repair of a hydraulic cylinder rod is used as a reference, with the DED-Arc scenario modeled using literature-based data under comparable conditions. The thesis also outlines the main process steps involved in DED-based repair, including surface preparation, material deposition, and post-processing, providing technical context for the environmental assessment. The findings indicate that the laser-based method resulted in significantly lower energy consumption and material losses compared to the arc-based alternative, primarily due to reduced overbuild and post-processing requirements. However, DED-LB also required substantially more shielding gas. The study highlights that environmental advantages depend strongly on part geometry, deposition volume, and process planning. While DED-LB demonstrated higher resource efficiency in the case studied, the results are not universally generalizable. The thesis underscores the importance of context-specific process selection in sustainable repair operations and encourages the integration of simplified LCA tools into industrial decision-making, while also recognizing their inherent limitations.
Keywords: Directed Energy Deposition, DED-Arc, DED-LB, additive repair, life cycle assessment, material efficiency, energy consumption, shielding gas, DED, LCA, sustainable manufacturing